Using Polygraph to Detect Passengers Carrying Illegal Items - Yu, Runxin; Wu, Si Jia; Huang, Audrey; Gold, Nathan; Huang, Huaxiong; Fu, Genyue; Lee, Kang (Frontiers in Psychology, 2019)
The present study examined the effectiveness of a Modified-Comparison Questions Technique, used in conjunction with the polygraph, to differentiate between common travelers, drug traffickers, and terrorists at transportation hubs. Two experiments were conducted using a mock crime paradigm. In Experiment 1, we randomly assigned 78 participants to either a drug condition, where they packed and lied about illicit drugs in their luggage, or a control condition, where they did not pack or lie about any illegal items. In Experiment 2, we randomly assigned 164 participants to one of the two conditions in Experiment 1 or an additional drug condition, where they packed and lied about a bomb in their luggage. For both experiments, we assessed participants’ RR interval, heart rate, peak-to-peak amplitude of Galvanic Skin Response and all three combined, using Discriminant Analyses to determine the classification accuracy of participants in each condition. In both experiments, we found decelerated heart rates and increased peak-to-peak amplitude of GSR in guilty participants when lying in response to questions regarding their crime. We also found accurate classifications of participants, in both Experiment 1 (drug vs control: 84.2% vs 82.5%) and Experiment 2 (drug vs control: 82:1% vs 95.1%; bomb vs control: 93.2% vs 95.1%; drug vs bomb: 92.3% vs 90.9%), above chance level. These findings indicate that Modified-CQT, in conjunction with the polygraph test, is a viable method for investigating suspects of drug trafficking and terrorism at transportation hubs such as train stations and airports.